Candida spp. associated with COVID-19 and its Susceptibility to some Antifungals - Mohammed Alkhuzaie; Neeran Obied Jasim (Al-Qadisiyah Journal of Pure Science, 2022)
This study aimed to conduct a survey of the Candida species associated with COVID-19 viral infection in 150 patients who were admitted to the intensive care unit (ICU) in Al-Diwaniyah Teaching Hospital in Al-Diwaniyah City, Iraq, for a five-month period from October 2021 to February 2022. The results indicated the dominance of Candida spp. over the rest of the isolated fungal species, with 97 isolates (64.66%). C. albicans was shown to be the most abundant species with a percentage of 55.67 percent (P 0.05), compared to the other Candida species that were isolated (Candida tropicalis 13.4 percent, Candida glabrata 12 percent, Candida krusie and Candida parapsilosis with 9.28 percent). In addition, we brought attention to the excellent action of the antifungals amphotericin B, itraconazole, and voriconazole, all of which have a high susceptibility rate.